Should All Complicated Appendicitis be Treated the Same? the Answer is No. Issue 10 (October 2019) - Wang, Victoria; Kriger, Diego; Fanous, Elias; Lee, Alfred; Zakhary, Bishoy; Coimbra, Raul; Depew, Aron J.
Delayed presentation of acute appendicitis is associated with increased complications. We hypothesized that the outcomes of appendectomy in delayed presentations of acute appendicitis (>72 hours of pain) were dependent on radiologic findings rather than late presentation. We reviewed records from 2009 to 2015 and analyzed delayed presentations of acute appendicitis. We divided patients into three groups based on specific CT findings: uncomplicated appendicitis (UA), phlegmon or abscess (PA), and other perforated appendicitis (PERF, signs of perforation without abscess or phlegmon). One hundred thirty-eight patients were included in this study (58 in the UA, 67 in the PA, and 13 in the PERF groups). Overall, 78 (57%) patients underwent early appendectomy (EA) and 60 (43%) underwent initial conservative management. The incidence of adverse events was lower in EA than that in initial conservative management (17% vs 42%, P = 0.005). EA in the UA group was associated with shorter hospitalization (3.2 vs 5.6 days, P < 0.001) and less adverse events (6% vs 29%, P < 0.05). Severe adverse events (two colectomies and one fecal fistula) were observed in the PA group. In conclusion, in these late presentations of appendicitis, complicated appendicitis was common. EA was safe in selected patients, however, and associated with decreased adverse events.